The political economy of Arab food sovereignty - Harrigan, Jane.; SpringerLink (Online service). (London : Palgrave Macmillan UK, 2014)
A political economy analysis of the history of food security in the Arab world, including the role played by the global food price crisis in the Arab Spring and the Arab response aiming at greater food sovereignty via domestic food production and land acquisition overseas - the so-called land grab.
Keywords: Science